Analysis of Traditional, Technological and Postmodernist Tendencies of the Modern Education System (Eurasian Research Bulletin, 2023)
This article analyzes the appearance, content and essence of modern educational development in the 21st century based on traditional, technological and postmodern trends. Types of modern education, their importance in the development of society, positive and negative aspects and paradigms are described. MIn our country, there is a need to improve cooperation between teachers and students based on the national traditions of Eastern education, humanitarian ideas, and to introduce the possibility of ensuring the intellectual development of developed countries based on the harmony of education and training.